DEVELOPMENT OF INTERMUNICIPAL COMMUNITY COOPERATION: STRATEGIC ALTERNATIVES - PANASENKO, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The relevance of the problem of ensuring the development of inter-municipal cooperation of territorial communities and in particular the strategizing of this process is revealed. The purpose of the study was to improve methodological recommendations for strategic planning of the development of inter-municipal community cooperation in Ukraine. It is shown that intermunicipal cooperation has a high potential for accumulation and effective use of local resources, ensuring social and economic development. It is pointed out that the development of inter-municipal cooperation of communities is able to ensure the achievement of real economic independence and self-sufficiency of territories, especially those communities that are currently subsidized or depressed. It is emphasized that inter-municipal cooperation of communities in the field of local economic development begins with the identification of partner communities and common economic interests. On this basis, specific business projects are defined, which will be implemented by joint efforts. It is substantiated that joint business projects are implemented in accordance with the defined goal. It is most appropriate to choose one of the four alternatives: (1) an expansive model of economic development, (2) an intensive growth model, (3) a diversification strategy, (4) an adaptive model of cooperation to ensure local economic development. Intermunicipal cooperation of two or more communities in the economic sphere should be interpreted as a separate business project. Under such an approach, its purpose, ultimate goals, measures to be implemented, and resources to be involved will be clearly defined.The project character of intermunicipal cooperation of communities is given by the fact that such cooperation is oriented, rather, towards achieving a certain common goal than stimulating economic development in one community.The scientific novelty of the research results lies in the further development of the methodological foundations of cooperation between territorial communities in the field of economics. The applied value of the research results lies in the formation of the algorithm of actions of local self-government bodies on the way to the development of innovative infrastructure to support innovative business.
Keywords: territorial communities; inter-municipal cooperation; community cooperation; local economic development; strategizing